A spoonful of L‐fucose—an efficient therapy for GFUS‐CDG, a new glycosylation disorder. Issue 9 (1st September 2021) - Feichtinger, René G; Hüllen, Andreas; Koller, Andreas; Kotzot, Dieter; Grote, Valerian; Rapp, Erdmann; Hofbauer, Peter; Brugger, Karin; Thiel, Christian; Mayr, Johannes A; Wortmann, Saskia B
Abstract: Congenital disorders of glycosylation are a genetically and phenotypically heterogeneous family of diseases affecting the co‐ and posttranslational modification of proteins. Using exome sequencing, we detected biallelic variants in GFUS (NM_003313.4) c.[632G>A];[659C>T] (p.[Gly211Glu];[Ser220Leu]) in a patient presenting with global developmental delay, mild coarse facial features and faltering growth. GFUS encodes GDP‐L‐fucose synthase, the terminal enzyme in de novo synthesis of GDP‐L‐fucose, required for fucosylation of N‐ and O‐glycans. We found reduced GFUS protein and decreased GDP‐L‐fucose levels leading to a general hypofucosylation determined in patient's glycoproteins in serum, leukocytes, thrombocytes and fibroblasts. Complementation of patient fibroblasts with wild‐type GFUS cDNA restored fucosylation. Making use of the GDP‐L‐fucose salvage pathway, oral fucose supplementation normalized fucosylation of proteins within 4 weeks as measured in serum and leukocytes. During the follow‐up of 19 months, a moderate improvement of growth was seen, as well as a clear improvement of cognitive skills as measured by the Kaufmann ABC and the Nijmegen Pediatric CDG Rating Scale. In conclusion, GFUS‐CDG is a new glycosylation disorder for which oral L‐fucose supplementation is promising. Synopsis: A novel type of congenital disorder of glycosylation (CDG) was identified in a child carrying biallelic variants in GDP‐L‐fucose synthase (GFUS). Oral L‐fucose supplementation resulted in clinical improvements. The index patient presented with stunted growth and no speech at the age of 3 6/12 years, coarse facial features, aversion to feeding, and recurrent vomiting on tube feeding. Biallelic variants in GFUS lead to a reduced level of GDP‐L‐fucose and subsequently to a general hypofucosylation of proteins. GFUS deficiency can be bypassed by oral L‐fucose supplementation triggering the salvage pathway for the generation of GDP‐L‐fucose. After the fucose therapy, the growth parameters have stabilized, and the patient started to speak and showed improved attention span and cognitive skills. Abstract : A novel type of congenital disorder of glycosylation (CDG) was identified in a child carrying biallelic variants in GDP‐L‐fucose synthase (GFUS). Oral L‐fucose supplementation resulted in clinical improvements.